2016
DOI: 10.1038/srep25296
|View full text |Cite
|
Sign up to set email alerts
|

A pseudouridylation switch in rRNA is implicated in ribosome function during the life cycle of Trypanosoma brucei

Abstract: The protozoan parasite Trypanosoma brucei, which causes devastating diseases in humans and animals in sub-Saharan Africa, undergoes a complex life cycle between the mammalian host and the blood-feeding tsetse fly vector. However, little is known about how the parasite performs most molecular functions in such different environments. Here, we provide evidence for the intriguing possibility that pseudouridylation of rRNA plays an important role in the capacity of the parasite to transit between the insect midgut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(88 citation statements)
references
References 38 publications
6
81
0
Order By: Relevance
“…Recent work has shown that pseudouridylation of a given position is not binary; instead a specific site can be more or less pseudouridylated in different conditions (Chikne et al 2016). If pseudouridylation does affect RNA turnover, the modest change we observed could be the result of only 25% of the pool of an RNA being pseudouridylated and showing differential stability, while the other 75% shows no change in stability, thereby dampening the signal.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Recent work has shown that pseudouridylation of a given position is not binary; instead a specific site can be more or less pseudouridylated in different conditions (Chikne et al 2016). If pseudouridylation does affect RNA turnover, the modest change we observed could be the result of only 25% of the pool of an RNA being pseudouridylated and showing differential stability, while the other 75% shows no change in stability, thereby dampening the signal.…”
Section: Discussionmentioning
confidence: 51%
“…The majority of indications that pseudouridylation plays an important biological role stems indirectly from the observation that Ψ's are modulated in response to different cellular conditions. Changes in the extent of rRNA pseudouridylation at specific sites changes with temperature and development, while entirely novel sites of pseudouridylation appear in snRNAs and mRNAs with stresses such as heat shock, starvation, oxidative stress, and immune stimulation (Wu et al 2011;Basak and Query 2014;Carlile et al 2014;Schwartz et al 2014;Li et al 2015;Chikne et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies have shown that active regulation of rRNA modification is a conserved behavior. For example, pseudouridylation of rRNA is up-regulated in the bloodstream form of the Trypanosoma brucei parasite (Chikne et al 2016), and rRNA methylation by NSUN5 regulates life span and stress resistance in flies, worms and yeast (Schosserer et al 2015). Similarly, a study in X. tropicalis showed that failure to ubiquitylate the ribosome biogenesis factors NOLC1 and TCOF1 destabilizes these proteins, and subsequently disrupts neural crest formation during cell differentiation (Werner et al 2015).…”
Section: Posttranscriptional Modification Of Rrnamentioning
confidence: 99%
“…Mapping the Pseudouridine nucleotides by the CMC method. Pseudouridine sites were mapped as previously described [90]. RNA from BAC16-mCherry-ORF45-infected iSLK cells and SLK cells that Figure S1.…”
Section: Methodsmentioning
confidence: 99%